The shortest path to the future Web - Ayers, Danny (2006)
This column's title could suggest that there is only one best path forward for the Web. The path begins with document metadata and travels through the world of microformats and embedded data. A waypoint is a semantic Web that leverages these approaches, along with those offered by an environment more capable of managing first-class data directly. This is only one path, however, and it probably isn't the shortest. The Internet is a rich environment with billions of active agents. Natural selection, mutation, and genetic breeding of sorts all happen to software systems, together with a significantly higher proportion of intelligent design than found in the real world. The net effect is that many different evolutionary paths are being explored simultaneously, and several could lead to a better Web.
Formato de archivo PDF.
IEEE Internet Computing, 2006, 10(6), pp. 76-79
Keywords: WEB SEMÁNTICA; WEB 2.0